THE VALUE OF THE NOTANGARA TRADITION AS A FORM OF SOCIAL CONTROL IN ADDRESSING JUVENILE DELINQUENCY - Annisa Kaili Biana; Azam Arifyadi; Ridwan Syahran; Hasan Hasan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The current phenomenon of juvenile delinquency in Palu City requires a restorative approach rooted in local values to complement formal legal mechanisms. This study aims to explore the values of the Notangara tradition within the Kaili ethnic group’s culture as a mechanism of social control. The primary focus of this study is to analyze how this tradition plays a role in reconstructing the character of adolescents through the principles of deliberation and kinship. This study employs a qualitative approach. Data were collected through participant observation and in-depth interviews with informants comprising traditional leaders, parents, and involved adolescents. Data analysis was conducted by referring to Travis Hirschi’s theory of social control, which encompasses four elements of social bonds: attachment, commitment, involvement, and belief. The research findings indicate that the Notangara tradition is effective in restoring social relationships fractured by adolescent delinquency. The traditional mediation process is able to rebuild adolescents’ attachment to their families and the community without resorting to stigmatization. The existence of traditional sanctions and a written statement reinforces adolescents’ commitment to adhering to social norms. Furthermore, this tradition integrates local moral values that reinforce individuals’ beliefs in behavior standards accepted by the community. The Notangara tradition is not merely a process of conflict resolution, but rather a form of preventive and curative social control rooted in local wisdom. The integration of Notangara values into guidance and counseling practices offers alternative intervention strategies for addressing deviant behavior. This study concludes that strengthening cultural identity through local traditions has a significant impact on the behavioral stability of adolescents amid the challenges of modernity.